Initiating and Cross-Linking Properties of Urea-Formaldehyde Oligomers with Peroxide Groups - Astakhova, Olena; Mykhailo Bratychak Jr.; Kohut, Ananiy (Видавництво Львівської політехніки, 2022)
Вивчені ініціюючі властивості пероксидних сечовино-формальдегідних олігомерів. Для порівняння вивчено ініціюючу активність у процесі полімеризації стирену пероксидним олігомером на основі епоксидного олігомеру Epidian-5 та трет.-бутилгідропероксиду. Структуруючі властивості сечовино-формальдегідних олігомерів з пероксидними групами вивчено на прикладі ненасичених олігоестерів. Хімізм процесу утворення продуктів просторово-зшитої будови досліджено з використанням ІЧ-спектроскопії.

The initiating properties of urea-formaldehyde oligomers with peroxide groups have been studied. For comparison, the initiating activity has been examined for the polymerization of styrene by the peroxide oligomer based on the epoxy oligomer Epidian-5 and tert-butyl hydroperoxide. The cross-linking properties of the urea-formaldehyde oligomers with peroxide groups have been investigated using unsaturated oligoesters as a model. The chemistry of the formation of the substances with a cross-linked structure has been studied using IR spectroscopy.
Ініціюючі та структуруючі властивості сечовино-формальдегідних олігомерів з пероксидними групами
Keywords: сечовино-формальдегідні олігомери; пероксид; стирен; ненасичені олігоестери; Epidian-5; ініціюючі та структуруючи властивості; ЕПР-метод; ІЧ-спектроскопія; urea-formaldehyde oligomers; peroxide; styrene; unsaturated oligoesters; Epidian-5; initiating and cross-linking properties; EPR method; IR spectroscopy